Los desafíos de los huracanes y la basura marina en islas. Estudio del huracán Iota en Providencia y Santa Catalina (2023)
The islands of Providencia and Santa Catalina are located in the Colombian Caribbean Sea and are highly representative of their biodiversity, coral reef and mangrove ecosystems. They are situated within the Seaflower Biosphere Reserve. This study aims to understand the distribution and quantities of marine litter on the beaches and mangroves of the islands, as well as the impacts of currents from Hurricane Iota. 32 points were used as reference, including mangroves, beaches (touristic and non-touristic/sand and gravel) and post-beach areas with vegetation. The investigation of marine litter followed established international protocols and quantified the waste in items per square meter. The results show that the tourist beaches remain in better condition than the non-tourist ones, resulting from human intervention framed in the use of the beach and the final disposal of waste. On the other hand, the passage of Hurricane Iota significantly altered the distribution of marine litter in some areas, with an increase of waste on touristic beaches (sand) and a decrease in post-beach areas with vegetation and mangroves. An increase in the number of marine litter items on touristic sandy beaches occurred due to the arrival of marine litter through coastal dynamics and the redistribution of marine litter present in the post-beach area. The mangrove sector showed a reduction in the number of marine litter items, which may be linked to factors such as vegetation degradation and possible redistribution of marine litter present due to coastal/marine dynamics and cleaning actions during the recovery processes of this ecosystem post-emergency. In the near future, an increase in the frequency and strength of extreme weather events is predicted, as well as an increase in the amount of plastic waste ending up in the sea. Therefore, continuous and long-term research is necessary.